Fraction of spectral solar irradiance transmitted through snow and sea ice as measured in different depths under sea ice (transmittance) at ROV station ODEN_AO2018_906-1 - Philipp Anhaus; Christian Katlein; Mario Hoppmann; Marcel Nicolaus (PANGAEA, 2020)
Measurements of transmitted irradiance under sea ice and corresponding incident solar radiation at the surface have been performed on multi-year ice during the Oden_AO18 campaign (Arctic Ocean 2018: MOCCHA – ACAS - ICE) Central Arctic / North Pole drift station between 19 August and 13 September 2018. The radiation measurements have been performed with Ramses spectral radiometes (TriOS, Rastede, Germany). All data are given in full spectral resolution interpolated to 1.0 nm, and integrated over the entire wavelength range (broadband, total: 320 to 950 nm). The irradiance sensor (cos-collector) was installed on the ROV. The transmittance is the ratio between transmitted irradiance and incident irradiance. All times are given in UTC.
In: Anhaus, P et al. (2020): Solar radiation over and under sea ice during the Oden_AO2018 campaign (Arctic Ocean 2018: MOCCHA - ACAS - ICE) Central Arctic / North Pole drift station in 2018 on IB ODEN [dataset bundled publication]. Alfred Wegener Institute, Helmholtz Centre for Polar and Marine Research, Bremerhaven, PANGAEA, https://doi.org/10.1594/PANGAEA.925698